Bi- and tri-valent T cell engagers deplete tumour-associated macrophages in cancer patient samples. Issue 1 (21st November 2019) - Scott, Eleanor M.; Jacobus, Egon J.; Lyons, Brian; Frost, Sally; Freedman, Joshua D.; Dyer, Arthur; Khalique, Hena; Taverner, William K.; Carr, Alison; Champion, Brian R.; Fisher, Kerry D.; Seymour, Len W.; et al.
Abstract : Background: Tumour-associated macrophages (TAMs) are often implicated in cancer progression but can also exert anti-tumour activities. Selective eradication of cancer-promoting (M2-like) TAM subsets is a highly sought-after goal. Here, we have devised a novel strategy to achieve selective TAM depletion, involving the use of T cell engagers to direct endogenous T cell cytotoxicity towards specific M2-like TAMs. To avoid "on-target off-tumour" toxicities, we have explored localising expression of the T cell engagers to the tumour with enadenotucirev (EnAd), an oncolytic adenovirus in Phase I/II clinical trials. Method: A panel of bi- and tri-valent T cell engagers (BiTEs/TriTEs) was constructed, recognising CD3ε on T cells and CD206 or folate receptor β (FRβ) on M2-like macrophages. Initial characterisation of BiTE/TriTE activity and specificity was performed with M1- and M2-polarised monocyte-derived macrophages and autologous lymphocytes from healthy human peripheral blood donors. T cell engagers were inserted into the genome of EnAd, and oncolytic activity and BiTE secretion assessed with DLD-1 tumour cells. Clinically-relevant ex vivo models (whole malignant ascites from cancer patients) were employed to assess the efficacies of the free- and virally-encoded T cell engagers. Results: T cells activated by the CD206- and FRβ-targeting BiTEs/TriTEs preferentially killed M2- over M1-polarised autologous macrophages, with EC50 values in the nanomolar range. A TriTE with bivalent CD3ε binding – the first of its kind – demonstrated enhanced potency whilst retaining target cell selectivity, whereas a CD28-containing TriTE elicited non-specific T cell activation. In immunosuppressive malignant ascites, both free and EnAd-encoded T cell engagers triggered endogenous T cell activation and IFN-γ production, leading to increased T cell numbers and depletion of CD11b + CD64 + ascites macrophages. Strikingly, surviving macrophages exhibited a general increase in M1 marker expression, suggesting microenvironmental repolarisation towards a pro-inflammatory state. Conclusions: This study is the first to achieve selective depletion of specific M2-like macrophage subsets, opening the possibility of eradicating cancer-supporting TAMs whilst sparing those with anti-tumour potential. Targeted TAM depletion with T cell engager-armed EnAd offers a powerful therapeutic approach combining direct cancer cell cytotoxicity with reversal of immune suppression.